Searching for and exploring double-parton scattering effects in four-jet production at the LHC - Rafał Maciuła; Antoni Szczurek (Physics Letters B, 2015)
We discuss four-jet production at the LHC. We calculate cross section for both single-parton scattering (SPS) using the ALPGEN code and for double-parton scattering (DPS) in leading-order collinear approach. Our results are compared with experimental data obtained recently by the CMS Collaboration. We show that the ALPGEN code relatively well describes distributions in transverse momenta and rapidity of each of the four jets ordered by their transverse momenta (leading, subleading, etc.). The SPS mechanism does not explain the distributions at large rapidity for the leading jet. The DPS mechanism improves the agreement with the experimental data in this corner of the phase space. In order to enhance the relative DPS contribution we propose to impose different cuts. The relative DPS contribution increases when decreasing the lower cut on the jet transverse momenta as well as when a low lower cut on the rapidity distance between the most remote jets is imposed. We predict very flat distribution in azimuthal angle between the most remote jets with low lower cuts on jets transverse momentum. We find phase-space corners where the DPS content is enhanced relatively to the SPS one.